2019
DOI: 10.1186/s12859-019-2855-9
|View full text |Cite
|
Sign up to set email alerts
|

Batch correction evaluation framework using a-priori gene-gene associations: applied to the GTEx dataset

Abstract: Background Correcting a heterogeneous dataset that presents artefacts from several confounders is often an essential bioinformatics task. Attempting to remove these batch effects will result in some biologically meaningful signals being lost. Thus, a central challenge is assessing if the removal of unwanted technical variation harms the biological signal that is of interest to the researcher. Results We describe a novel framework, B-CeF, to evaluate the effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 28 publications
1
40
1
Order By: Relevance
“…circumstances) is based on a four-point Hardy Scale. The ventilator death group samples were analysed since it had significantly shorter ischemic times, which preserve sample quality 41 . Our previous work 41 showed that using some common methods for adjusting the heterogenous GTEx expression data for hidden confounding factors (e.g., using principle components) filters out many of the biological signals-which is relevant here.…”
Section: Confounding Factors Adjustment the Type Of Death Classificamentioning
confidence: 99%
See 2 more Smart Citations
“…circumstances) is based on a four-point Hardy Scale. The ventilator death group samples were analysed since it had significantly shorter ischemic times, which preserve sample quality 41 . Our previous work 41 showed that using some common methods for adjusting the heterogenous GTEx expression data for hidden confounding factors (e.g., using principle components) filters out many of the biological signals-which is relevant here.…”
Section: Confounding Factors Adjustment the Type Of Death Classificamentioning
confidence: 99%
“…The ventilator death group samples were analysed since it had significantly shorter ischemic times, which preserve sample quality 41 . Our previous work 41 showed that using some common methods for adjusting the heterogenous GTEx expression data for hidden confounding factors (e.g., using principle components) filters out many of the biological signals-which is relevant here. Thus ComBat 42 from the R/Bioconductor package sva 42 was used to adjust for known confounding factors, which has been shown to outperform other methods 41 .…”
Section: Confounding Factors Adjustment the Type Of Death Classificamentioning
confidence: 99%
See 1 more Smart Citation
“…As GTEx data is known to be subject to multiple confounding factors (batch effect, experimental bias, read contamination, etc.) [43,44,25], a partial PCcorrection [25] was applied to correct the data (Additional file 1.3). To investigate the aging process two subsets representing contrasting age classes were selected from the corrected data set: 73 samples between 20 and 30 years old (referred as young in this report), and 292 samples between 60 and 70 years old (referred as old in this report).…”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent with recent results that caution against the use of latent factor correction when applying coexpression analysis in highly heterogeneous tissues such as brain. 31 To ensure modules are not driven by brain-involved diseases or atypical sample outliers, we exclude individuals on the basis of their known medical conditions at time of death, principal-component outliers, and sample-sample connectivity outliers (Methods, Suppl. Table 1).…”
Section: Building Robust Human Co-expression Networkmentioning
confidence: 99%